Project-based training for teachers at vocational schools to prepare online modules in West Sumatra - Hasan Maksum; Wawan Purwanto; Martias Martias; Syalsa Billa Ahmad (Universitas Muhammadiyah Magelang, 2023)
The transition period between the pandemic and after it requires strategies so that learning transitions continue to create comfort for students in learning. The purpose of this activity is to help teachers become more experts at creating online modules. This activity involved 30 participants from members of the West Sumatra Automotive Engineering Subject Teacher Consultation. Participants' online module work will be analyzed to determine the teacher's ability to design online modules and the effectiveness of the learning process. Participants can effectively create learning modules as a result. However, instructors must spend more time teaching online students on how to complete assignments.